2003
DOI: 10.1038/sj.bjc.6600816
|View full text |Cite
|
Sign up to set email alerts
|

How doctors record breaking bad news in ovarian cancer

Abstract: Revealing the diagnosis of cancer to patients is a key event in their cancer journey. At present, there are no minimal legal recommendations for documenting such consultations. We reviewed the Hospital records of 359 patients with epithelial ovarian cancer in the Mersey Area between 1992 and 1994. We identified the following factors: age, hospital, postcode, surgeon, stage of disease and survival. These were compared to information recorded at the time of the interview such as person present, descriptive words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Relatives often ask that a serious diagnosis be withheld from older people, 3 and physicians sometimes collude with them in maintaining secrecy. 13 However, several reports 3,14 have shown that agreement between the preferences of relatives and those of patients regarding truth disclosure was not significantly greater than that expected by chance alone. For example, we have found that three quarters of relatives who asked that a patient not be told of their diagnosis were in conflict with the patient's wishes.…”
Section: Discussionmentioning
confidence: 92%
“…Relatives often ask that a serious diagnosis be withheld from older people, 3 and physicians sometimes collude with them in maintaining secrecy. 13 However, several reports 3,14 have shown that agreement between the preferences of relatives and those of patients regarding truth disclosure was not significantly greater than that expected by chance alone. For example, we have found that three quarters of relatives who asked that a patient not be told of their diagnosis were in conflict with the patient's wishes.…”
Section: Discussionmentioning
confidence: 92%
“…Two retrospective studies retrieved the prognostic communication details while in-person telephonic interviews were conducted in two studies using medical records. 34 36 In comparison, the combination of methods such as interviews and records or interviews and ward observation or interview and home visits was used in five studies. 8 , 18 , 37 , 38 Almost all the studies with face-to-face or telephonic interviews used audiotaped recordings of verbatim of the triad involved, and subsequently, most of the qualitative studies used grounded theory procedures for analysis of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of 126 articles were screened. A total of 27 studies fulfilled eligibility criteria and were thus eligible for inclusion in this systematic review and meta‐analysis 2,3,8‐32 . Table 1 shows the characteristics of included studies with the prevalence of collusion.…”
Section: Resultsmentioning
confidence: 99%